Measurement of serum hepatitis B surface antibody levels in Iranian autistic children and evaluation of immunological memory after booster dose injection in comparison with controls. Issue 7 (27th February 2019) - Barfi, Shahram; Narges, Chimeh; Pouretemad, Hamid Reza; Poortahmasebi, Vahdat; Norouzi, Mehdi; Farahmand, Mohammad; Yahyapour, Yousef; Ghorbani, Saeid; Ghalichi, Leila; Ofoghi, Haleh; Jazayeri, Seyed Mohammad
Abstract: Background: Responsiveness to hepatitis B vaccine among patients with autism spectrum disorders (ASD) has not been evaluated worldwide. We aimed to determine the anti‐HBs antibody duration in autistic and healthy children few years after primary vaccination and evaluate their immunological memory against hepatitis B virus (HBV) vaccine with booster dose administration. Methods: One hundred seven and 147 HBsAg‐negative children from ASD and normal population were recruited, respectively. HBV seromarkers (HBc‐Ab, HBsAg, and HBs‐Ab) were assessed and subsequently, molecular tests were used on all the subjects. A booster dose of vaccine was injected for those who showed low levels (<10 mIU/mL) of anti‐HBs and their antibody levels was measured 4 weeks later. Results: The mean ages of ASD and control groups were 7.14 ± 2.42 and 8.68 ± 1.96, respectively. Seven (6.5%) of the ASD group were positive for anti‐HBc and one child was positive for occult hepatitis B infection (HBsAg negative, HBV DNA positive). In ASD, 54 (50.4%) and 53 (49.6%) had adequate (>10 mIU/mL) and low anti‐HBs levels, respectively. Among control group, 74 (50.4%) and 73 (49.6%) had sufficient and low antibody levels, respectively. After injection of a booster dose for all children with low antibody, 100% of ASD and 92% (59 of 64) of control pupils contained >10 mIU/mL of antibody, respectively. In both the groups, the HBs‐Ab titer increased similarly in response to the booster injection ( P  < 0.05). Conclusion: Despite previous investigations regarding immune impairment in individuals with autism, the immune system of these individuals was able to manage the hepatitis B vaccine challenge.